2021
DOI: 10.7150/ijbs.61717
|View full text |Cite
|
Sign up to set email alerts
|

Single-cell RNA sequencing reveals spatiotemporal heterogeneity and malignant progression in pancreatic neuroendocrine tumor

Abstract: Aims: Using Single-cell RNA sequencing (scRNA-seq), we explored the spatiotemporal heterogeneity of pancreatic neuroendocrine tumors (pNETs) and the underlying mechanism for malignant progression. Methods: scRNA-seq was conducted on three tumor tissues (two primary tissues from different sites, one liver metastatic lesion), one normal liver tissue, and peripheral blood mononuclear cells from one patient with a metastatic G2 pNET, followed by bioinformatics analysis and validation in a pNETs cohort. Results: Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 62 publications
1
23
0
Order By: Relevance
“…Pancreatic NETs have temporal heterogeneity, which refers to changes in a tumor's genetic variety over time, particularly while it is being treated (Lou, Qin, Xu, Yu, & Ji, 2022). scRNA-seq analysis revealed intra-and intertumor heterogeneities in cell populations, transcriptional states, and intercellular communications among primary and metastatic lesions of pNETs (Zhou et al, 2021). Nevertheless, the most important consideration is to nd the subgroup with high metastatic potential, screen its markers, and perform targeted treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pancreatic NETs have temporal heterogeneity, which refers to changes in a tumor's genetic variety over time, particularly while it is being treated (Lou, Qin, Xu, Yu, & Ji, 2022). scRNA-seq analysis revealed intra-and intertumor heterogeneities in cell populations, transcriptional states, and intercellular communications among primary and metastatic lesions of pNETs (Zhou et al, 2021). Nevertheless, the most important consideration is to nd the subgroup with high metastatic potential, screen its markers, and perform targeted treatment.…”
Section: Discussionmentioning
confidence: 99%
“…An original article published in GUT revealed the genomic intertumoral heterogeneity of PanNETs (Gill et al, 2019). Zhou Y et al described intra-and intertumor heterogeneities in PanNET cell populations by single-cell sequencing (Zhou et al, 2021). However, based on the heterogeneous characteristics of PanNETs, it is important to identify speci c subsets with high metastatic potential and to identify precise metastasis markers for guiding clinical work.…”
Section: Introductionmentioning
confidence: 99%
“…It is more abundant in the metastatic foci in the liver than in primary lesions for insulinomas [ 17 ]. Single-cell sequencing of a pancreatic NET (G2) from the same patient [ 18 ] showed that macrophages could be divided into five clusters that are different from the classic M1 and M2 clusters. Among these clusters, cluster one is mainly located in the primary site, clusters two and five only exist in liver metastases, while chemokine CCL13 is only expressed in cluster one, and SPP1 is only present in clusters two and five.…”
Section: Innate Immune Cellsmentioning
confidence: 99%
“…The single-cell RNA sequencing of pancreatic NET (G2) from the same patient revealed that fibroblasts could be roughly divided into inflammatory, antigen-presenting, and myofibroblastic cancer-associated fibroblasts, some of which include inflammatory subtypes that can secrete cellular senescence factors [ 18 ]. It also found that the TME of primary tumors contained more heterogeneous fibroblast clusters than those of liver metastases; however, there were also fibroblasts specific to liver metastases [ 18 ]. The crosstalk between NEN cells and fibroblasts induces excessive fibrosis, and the most common example of fibrosis is mesenteric fibrosis.…”
Section: Other Cells and Molecules In Tmementioning
confidence: 99%
“…Despite significant advances in the understanding and treatment of many cancers, pancreatic cancer (PC) remains one of the deadliest and most difficult forms of cancer to manage. Approximately 20% of newly diagnosed PC cases worldwide arise in China (1,2). The primary approaches to treating PC include surgical resection and chemotherapy (3), but the emergence of chemoresistance represents a major barrier to effective patient treatment.…”
Section: Introductionmentioning
confidence: 99%